2021
DOI: 10.1002/gcc.22992
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent loss of chromosome 22 and SMARCB1 deletion in extra‐axial chordoma: A clinicopathological and molecular analysis

Abstract: Extra-axial chordoma is a rare neoplasm of extra-axial skeleton and soft tissue that shares identical histomorphologic and immunophenotypic features with midline chordoma. While genetic changes in conventional chordoma have been well-studied, the genomic alterations of extra-axial chordoma have not been reported. It is well known that conventional chordoma is a tumor with predominantly non-random copy number alterations and low mutational burden. Herein we describe the clinicopathologic and genomic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…147 Of note, heterozygous deletion of SMARCB1 has been described in some conventional chordomas, including extra-axial tumours. 148,149 Loss of INI1 expression, while necessary for the diagnosis of poorlydifferentiated chordoma, is not entirely specific and has been reported in rare conventional and dedifferentiated chordomas. 144 The diagnosis of poorlydifferentiated chordoma thus requires both the appropriate histologic and immunophenotypic features.…”
Section: H O R D O M Amentioning
confidence: 99%
See 1 more Smart Citation
“…147 Of note, heterozygous deletion of SMARCB1 has been described in some conventional chordomas, including extra-axial tumours. 148,149 Loss of INI1 expression, while necessary for the diagnosis of poorlydifferentiated chordoma, is not entirely specific and has been reported in rare conventional and dedifferentiated chordomas. 144 The diagnosis of poorlydifferentiated chordoma thus requires both the appropriate histologic and immunophenotypic features.…”
Section: H O R D O M Amentioning
confidence: 99%
“…EWSR1 can be codeleted due to its proximity to SMARCB1 , leading to complex FISH patterns that may be mistaken for EWSR1 rearrangement 147 . Of note, heterozygous deletion of SMARCB1 has been described in some conventional chordomas, including extra‐axial tumours 148,149 . Loss of INI1 expression, while necessary for the diagnosis of poorly‐differentiated chordoma, is not entirely specific and has been reported in rare conventional and dedifferentiated chordomas 144 .…”
Section: Introductionmentioning
confidence: 99%
“…Poorly differentiated chordomas are characterized by the loss of INI1 / SMARCB1 and may also represent a discrete entity with a more aggressive phenotype, which is more similar to rhabdoid tumors. However, driver gene alterations are critical in tumor initiation and progression, but may not be involved in tumor dedifferentiation and high-grade transformation ( 82 ).…”
Section: Leap To the Next Generation: Advances In Genetic Researchmentioning
confidence: 99%
“…Recent studies have described the immunohistochemical loss of SMARCB1/INI1 protein in poorly differentiated chordoma associated with SMARCB1 gene deletions at fluorescence in situ hybridization (FISH) examination, mainly deriving from large, homozygous deletions at 22q11 locus (4,(6)(7)(8). The loss of SMARCB1/INI1 protein could potentially serve as theoretical basis for evaluating the efficacy of new targeted therapies, i.e., Enhancer of Zeste homologue 2 (EZH2) inhibitors (Tazemetostat), histone deacetylase inhibitors, and CDK4 inhibitors (4,7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have demonstrated that conventional chordomas are characterized by very low to modest mutation burden, and are mainly characterized by large copy number loss, typically involving chromosomes 1p, 3, 9q, 10, 13, and 14, and a small number of copy number gains on chromosome 7 and 1q (4,9). Loss of chromosome 22 and/or heterozygous deletion of SMARCB1 seems to be a rare event in conventional chordomas, although data are referred to small series (4,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%